(untitled) (Bangladesh Pharmaceutical Journal, 2020)
As one of the fundamental human rights, healthcare is usually sought during illness episode. A questionnaire-based survey was conducted on 221 residential university students to identify the existing disease patterns and treatment seeking behaviors. Among the students, 22.17% were devoid of normal body-weight and 45.7% of them exercise at least three days a week. Based on smoking habits they were non-smoker (60.18%), smoker (25.34%), and second-hand smoker (14.48%). Besides, 33.03% of them have an allergy (seasonal: 24.43%; perennial: 8.60%) and 75.11% of students’ family members have or had at least one of the eight specified diseases. In 2019, around 98% of the students had suffered from at least one illness like fever-all types (86.43%), common cold (52.94%), diarrhea (20.36%), cough (46.61%), nasal congestion (10.86%), pain/aches-all types (25.79%), gastric problems (49.32%), skin diseases (15.38%), dental diseases (1.36%), eye diseases (0.9%), and many other diseases (4.52%). To mitigate these illnesses majority took medications instead of self-recovery that was highest for dental and eye diseases (100%), and lowest for cough (58.25%) and nasal congestion (58.33%). Usually, 61.99% of the residents go to Government Hospital (DMCH: 45.70%, BSMMU: 9.95%) for seeking treatment followed by University Medical Center (41.63%), Private Medical Consultant (5.88%), Private Hospital (4.52%), and others (3.62%). Moreover, 67.42% of the students take prescribed medicines as stated in prescriptions. As there is a tendency among 83.26% of the students to take medicines without prescriptions, raising awareness on the detrimental impacts of self-treatment is needed to refrain them from self-medication practices. Bangladesh Pharmaceutical Journal 23(2): 187-194, 2020